Removal of highly dispersive microspheres from wastewater using modified spirulina hetero-coagulation and their application in flame retardancy. Issue 3 (5th January 2022) - Zheng, Gaoda; Cai, Zhihao; Yu, Ziyi; Yang, Yuqin; Ye, Hui; Qin, Zheng; Zhang, Shiyu; Zuo, Xiaobing
Abstract : There is an urgent demand to find an effective solution to microplastic pollution in water. Abstract : There is an urgent demand to find an effective solution to microplastic pollution in water. In addition, the harm of algal flooding to water quality also haunts human society because of the increase of industrialization. In this work, modified spirulina (T-spirulina) is used to destroy the electrostatic double-layer structure of microspheres by a hetero-coagulation process, completely removing highly dispersed poly(tetrafluoroethylene) (PTFE/PSAN) microspheres from water. Experimental results indicate that the PTFE/PSAN microspheres could be controllably deposited on the surface of T-spirulina with the assistance of formic acid. T-Spirulina absorbs at least three times its own mass of PTFE/PSAN microspheres and the removal efficiency of the highly dispersed microspheres in water is even up to 99.81 wt%, which is better than that of other demulsifiers. Due to the fact that T-spirulina is rich in nitrogen and phosphorus elements, the hetero-coagulation product (STP) has great potential in the field of flame retardants. The thermogravimetric analysis (TGA) tests show that the addition of STP could improve the flame retardant performance of an epoxy resin (EP) matrix. Meanwhile, the limiting oxygen index (LOI) and vertical combustion performance are also improved with an increase of the amount of PTFE/PSAN coating used. With the addition of 5 wt% of STP, the LOI value of the composite increased up to 22.8. Cone calorimetry shows that HRR, CO and CO2 production are significantly decreased with the STP10 composite, which is much lower than that of neat EP.